APLIKASI TETANDINGAN BANTEN PEJATI BERBASIS ANDROID - Kadek Yoga Wira Putra; I Gede Mahendra Darmawiguna; I Ketut Resika Arthana (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
The objective of this research was using technology in developing the application as interactive and interesting media in introducing Tetandingan Banten Pejati. So that The application could attract the reader to safe and learn Bali traditional culture and especially metetandingan banten.Banten Pejati application based on android was developed by using a software life cycle on sequential linier or waterfall. The development of this program is using unified modeling language and implementing on JAVA language using Eclipse, plug-ins ADT (Android Development Tools) and AndEngine as extra library and Blander 2.69 application for implemented animation videos.The result of this research is a Banten Bali Application based on android that feature an animated video of how to create “banten”. The whole function have successfully implemented based on the plan.